2014
DOI: 10.1007/s11274-014-1789-7
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of hexachlorobenzene by a constructed microbial consortium

Abstract: A consortium comprised of an engineered Escherichia coli DH5α and a natural pentachlorophenol (PCP) degrader, Sphingobium chlorophenolicum ATCC 39723, was assembled for degradation of hexachlorobenzene (HCB), a persistent organic pollutant. The engineered E. coli strain, harbouring a gene cassette (camA (+) camB (+) camC) that encodes the F87W/Y96F/L244A/V247L mutant of cytochrome P-450cam (CYP101), oxidised HCB to PCP. The resulting PCP was then further completely degraded by ATCC 39723. The results showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Under aerobic conditions, HCB could be degraded into pentachlorophenol, tetrachlorohydroquinone, and 2,6-dichlorohydroquinone by certain microbes. 30,31 Although previous studies reported that soil amendment with biochar could enhance the degradation of organic contaminants (e.g., PAHs and benzonitrile), it was ascribed to the nutritional stimulation of microbes by the biochar. 32,33 Far more research has concluded that biochar mainly inhibits the dissipation of organic contaminants in soil due to its strong sorption ability.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under aerobic conditions, HCB could be degraded into pentachlorophenol, tetrachlorohydroquinone, and 2,6-dichlorohydroquinone by certain microbes. 30,31 Although previous studies reported that soil amendment with biochar could enhance the degradation of organic contaminants (e.g., PAHs and benzonitrile), it was ascribed to the nutritional stimulation of microbes by the biochar. 32,33 Far more research has concluded that biochar mainly inhibits the dissipation of organic contaminants in soil due to its strong sorption ability.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The dissipation of HCB in the control treatment during preplanting incubation might be partly ascribed to the degradation of HCB by soil microbes, as well as to the volatilization of HCB since it was newly spiked into the soil and incubated in an unsealed pot. Under aerobic conditions, HCB could be degraded into pentachlorophenol, tetrachlorohydroquinone, and 2,6-dichlorohydroquinone by certain microbes. , Although previous studies reported that soil amendment with biochar could enhance the degradation of organic contaminants (e.g., PAHs and benzonitrile), it was ascribed to the nutritional stimulation of microbes by the biochar. , Far more research has concluded that biochar mainly inhibits the dissipation of organic contaminants in soil due to its strong sorption ability …”
Section: Resultsmentioning
confidence: 99%
“…We used a co‐culture approach to synthesize arsenic sulfide nanomaterials: an E. coli strain expressing arsenate reductases from ANA‐3 and another E. coli strain expressing thiosulfate reductase from Salmonella enterica were used. Similar to our approach, reseachers used an engineered E. coli strain and Sphingobium chlorphenolicum for the bioremediation of hexachlorobenzene (Yan et al ., ). A shift towards division of labour and the implementation of co‐cultures for bioprocessing has been explored in recent publications using synthetic microbial communities (Kim et al ., ; Lindemann et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Regarding degradation, analysis of the catabolic pathways in natural strains facilitates the migration of functional genes to artificial cells that do not possess efficient or complete degradation abilities ( 5, 7 ). For example, an artificial consortium of three E. coli BL21(DE3) strains with synergistic functional modules was designed to completely degrade phenanthrene ( 8 ), and the pathway of engineered E. coli DH5α was linked with a natural pentachlorophenol degrader to mineralize hexachlorobenzene ( 9 ). Additionally, restraining their proliferation is one of the primary challenges for genetically modified microorganisms.…”
Section: Introductionmentioning
confidence: 99%